Virtual screening studies to identify novel inhibitors for Sigma F protein of Mycobacterium tuberculosis. Issue 4 (December 2015) - Mustyala, Kiran Kumar; Malkhed, Vasavi; Chittireddy, Venkataramana Reddy; Vuruputuri, Uma
Abstract: Tuberculosis (TB) is one of the oldest threats to public health. TB is caused by the pathogen Mycobacterium tuberculosis (MTB). The Sigma factors are essential for the survival of MTB. The Sigma factor Sigma F (SigF) regulates genes expression under stress conditions. The SigF binds to RNA polymerase and forms a holoenzyme, which initiates the transcription of various genes. The Usfx, an anti-SigF protein, binds to SigF and alters the transcription initiation and gene expression. In the present work, virtual screening studies are taken up to identify the interactions between SigF and small molecular inhibitors which can inhibit the formation of holoenzyme. The studies reveal that ARG 104 and ARG 224 amino acid residues of SigF protein are forming important binding interactions with the ligands. The in silico ADME properties for the ligand data set are calculated to check the druggability of the molecules.